Características sociodemográficas e comportamento de risco à saúde em adolescentes de Aracaju e região metropolitana e revisão sistemática sobre programas de intervenção em atividade física - Soares, Nara Michelle Moura (2016)
Objective: To estimate the prevalence of risk behaviors to health and its association with sociodemographic characteristics among adolescents in Aracaju and the metropolitan area, Sergipe, Brazil to the investigation and present evidence regarding the existence of intervention programs in physical activity for adolescents through of a systematic review. Methods: For the survey research, the sample consisted of 2207 adolescents (13 to 18 years) enrolled in public schools of the municipalities that make up the observed region. The survey information was held electing the following behaviors: "low levels of physical activity" and "watching time TV/day", through the PAQ-C, "drinking", "consumption of more than five doses of alcohol on a single occasion", "involvement in fights", "cigarette smoking", "bear arms" and "marijuana use", identified by YRBS instrument and "economic class" accessed for ABEP. For the systematic review, surveys were conducted in PubMed, SportDiscus, Lilacs and SciELO from keywords to population identification, intervention and outcome, with the DeCS and MeSH terms in English, Portuguese and Spanish. They included observational studies with minimal intervention six months, minimum sample size of 100 teenagers, written in any language and have reached the score STROBE ≥ 70%. Results: The highest prevalence was found for "low levels of physical activity" (88.1%), followed by "watch more than two hours of TV a day" (66.2%) and "alcoholic beverages" (38.0%). There are different patterns of risk behaviors sexes. female is associated with "low levels of physical activity" and "more than two hours watching TV." Male gender was associated with "weapons of transport", "involvement in fights" and "marijuana use". The largest age group of 16 years was associated with the "cigarette smoking", "drinking", "consuming more than five drinks of alcohol during" and "marijuana use." The highest socioeconomic status was associated with "weapons of transport", "involvement in fights", "drinking" and "more than five doses of alcohol on the occasion". In the systematic review, only seven studies met all inclusion criteria. Five studies presented different approaches to measure the physical activity intervention using the school environment only for sample recruitment, with strategies favorable to physical activity levels, and effective in promoting an active lifestyle outside of school. Conclusion: In the survey study, the most prevalent variables were: low levels of physical activity, more than two hours watching TV and drinking. The behaviors were less prevalent marijuana use, transport of weapons, cigarette smoking and involvement in fights. Associations were observed in the studied population with three risk groups that should be highlighted: male, from 17 years and with high socioeconomic status. A Systematic Review found that, among the analyzed studies, most presented experimental study design, with follow-up up to one year, with interventions that linked physical activity to diet/nutrition, with different implementation strategy and implemented in extracurricular environments, able to promote change in health risk behavior in adolescents.